Analysis of Bovine Spermatozoa CSP-Gene Expression using qPCR and Relative Quantification Method as Biodiagnostic Tool for Fertilizing Capacity - H Ismail, N; F Syed Mohamad, S; H F Jaafar, F; Osman, K; Z Mohd Yusof, F; F Ibrahim, S (International Journal of Engineering and Technology, 2019)
Gene expression studies enable for real-time relative quantification of expressed genes. However, the incorporation of a primary discerning tool before amplification for specific sequences of genes of interest is yet to be implemented. The amplification of gene sequences from discriminate sample groups further enhances the results following qPCR and provides an absolute exclusive measurement for the defined sample. Cryopreserved spermatozoa have characteristics of compromised sperm quality as the cells are exposed to a rapid temperature downshift not normally encountered by such cells in vivo. Thus, the use of a separation system before cryopreservation produces a refined outcome in gene expression studies. The proliferation of Cold Shock Protein (CSP) can relatively be quantified by conducting qPCR following sperm selection and cryopreservation. CSPs are indicators of cells adapting to the decrease in temperature and indirectly acts as an intracellular protective mechanism for the cell. The current study compares the effects of sperm selection system in isolating a homogeneous population of spermatozoa for cryopreservation followed by quantification of CSP gene. Method of molecular assessment involved quantifying the amplified sequences via qPCR and gene expression following sperm isolation was significant in increasing spermatozoa viability by 26.2% (P< 0.05). The relative fold expression of CSP gene for treatment group increased from 1.00 fold to 1.38 fold. The Cq values for treatment group had recorded an earlier point of amplification (Cq= 24.87) as compared to control Cq= 25.83. Our findings suggest that the use of a sperm isolation system before cryopreservation would increase the probability of obtaining higher amplifications of CSP genes that would confer protection against extremely low temperatures during cryopreservation. This would increase the likelihood of in vitro fertilization using cryopreserved spermatozoa by implementing qPCR as a potential biomolecular diagnostic tool to ascertain the fertilizing potential of the spermatozoa.Â Â